THE EFFECTS NEUROPROTECTION OF TELMISARTAN ON STROKE WITH HYPERTENSION - Ernawati, Iin; Hidayati, Hanik Badriyah; ., Sumarno (Malang Neurology Journal, 2020)
Stroke is the second deadly disease in the world after ischemic heart disease. According to data of RISKESDAS (Riset Kesehatan Dasar), stroke was the highest cause of death in Indonesia in 2013. Hypertension is the one of the most important risk factors for stroke. Hypertension therapy is done by modification and the use of antihypertensives. The antihypertensives used is Telmisartan which is a class of Angiotensin Receptor Blocker (ARB) that works by inhibiting bind to angiotensin II type receptors that is angiotensin II type 1 receptors (AT-1R) which directly make angiotensin II bind to AT-2R (angiotensin receptor type 2 receptors). Telmisartan has a neuroprotectant effect that works by inhibiting the appearance of inflammatory cytokines, production of ROS (Reactive Oxygen Species), PGE2 (prostaglandin E2) and NMDA (N-Methyl-D-Aspartate) activity. Telmisartan activates PPAR-gamma (PPAR-Î³), which is very useful in carbohydrate and lipid metabolism which directly protect blood vessels. Telmisartan has the advantage of structure and pharmacokinetics that support the effects of nerve protection. Based on lipophilicity and chemical structure, Telmisartan easily penetrates the brain barrier and high affinity to PPAR-Î³, supporting the effects of Telmisartan neuroprotection. Based on pharmacokinetic aspects, telmisartan has the advantage of having a rapid onset that ranges from 30-60 minutes, with T Â½ (half life) elimination is 24 hours. T 1/2 elimination for up to 24 hours from Telmisartan is clinically beneficial to improve medication adherence.